(untitled) (Eurasian Journal of Ecology, 2025)
The ecotoxicological evaluation of Ile Alatau headwaters is extremely important for South-East Kazakhstan as mountain cryoshpere provide gross of water sources that supply Almaty agglomeration and surrounding industrial and agricultural areas of Almaty region. In the current study, the toxic potential of surface water of two gorges, namely Kuygensay gorge located directly above Almaty city and referenced Orta Turgen gorge, including moraine lakes, alpine lake, springs and main current at altitudes 2400 – 3500 m above sea level, was assessed by acute D.magna toxicity test according to OECD guideline. No significant toxicity was shown for water samples from Orta Turgen high-altitude tributaries and alpine lakes, whereas Titov moraine lake (the very source of Kuygensay river), main current and tributary spring of river Kuygensay demonstrated significant toxicity toward young daphnids in acute tests. The indexation based on D.magna immobilization/mortality data scoring, showed that headwaters of river Kuygensay are considered to meet “moderately toxic” to “toxic” class of toxicity, and Almaty agglomeration is probably the main source of pollution. These data provide opportunity to further investigation on pollution of glaciers and high-altitude water resources of Ile Alatau mountain range. Key words: high-altitude water sources, D.magna, bioassay, toxicity assessment, Ile Alatau